Bronchoscopic lung volume reduction coil treatment for severe emphysema: a systematic review and meta-analysis of individual participant data - Roodenburg, Sharyn; Hartman, Jorine E.; Deslée, Gaëtan; Herth, Felix; Klooster, Karin; Sciurba, Frank; Shah, Pallav; Valipour, Arschang; Zoumot, Zaid; Slebos, Dirk-Jan (Respiration, 2022)
Background: Lung volume reduction coil (LVR-coil) treatment provides a minimally invasive treatment option for severe emphysema patients which has been studied in multiple clinical trials. Objectives: The aim of the study was to assess the effect of LVR-coil treatment on pulmonary function, quality of life, and exercise capacity using individual participant data. Method: PubMed, Web of Science, and EMBASE were searched until May 17, 2021. Prospective single-arm and randomized controlled trials that evaluated the effect of LVR-coil treatment on forced expiratory volume in 1 s (FEV1), residual volume (RV), St. George Respiratory Questionnaire (SGRQ) total score, and/or 6-min walk distance (6MWD) and were registered in an official clinical trial database were eligible for inclusion. Individual patient data were requested, and a linear mixed effects model was used to calculate overall treatment effects. Results: Eight trials were included in the final analysis, representing 680 individual patients. LVR-coil treatment resulted in a significant improvement in FEV1 at 3- (0.09 L [95% confidence interval (95% CI): 0.06-0.12]) and 6-month follow-up (0.07 L [95% CI: 0.03-0.10]), a significant reduction in RV at 3- (−0.45L [95% CI: −0.62 to −0.28]), 6- (−0.33L [95% CI: −0.52 to −0.14]), and 12-month follow-up (−0.36L [95% CI: −0.64 to −0.08]), a significant reduction in SGRQ total score at 3- (−12.3 points [95% CI: −15.8 to −8.8]), 6- (−10.1 points [95% CI: −12.8 to −7.3]), and 12-month follow-up (−9.8 points [95% CI: −15.0 to −4.7]) and a significant increase in 6MWD at 3-month follow-up (38 m [95% CI: 18-58]). Conclusions: LVR-coil treatment in emphysema patients results in sustained improvements in pulmonary function and quality of life and shorter lived improvements in exercise capacity. Since the owner of this LVR-coil has decided to stop the production and newer generations LVR-coils are currently being developed, these results can act as a reference for future studies and clinical guidance.
Online veröffentlicht: 11. April, 2022
Gesehen am 20.06.2023